4‐CH3CONH–TEMPO/Peracetic Acid System for a Shortened Electron‐Transfer‐Cycle‐Controlled Oxidation of Secondary Alcohols1. Issue 12 (3rd June 2015) - Zhang, Shufang; Miao, Chengxia; Xia, Chungu; Sun, Wei
Abstract We have developed a 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO) derivative catalyzed oxidation of secondary alcohols with peracetic acid as the oxidant, which was generated from H2O2 and acetic acid catalyzed by strongly acidic resins. The oxidation of alcohols proceeded well through a shortened electron‐transfer cycle under metal‐free conditions, avoiding the use of any other electron‐transfer mediators such as halides. In addition, we demonstrated that the present system exhibited excellent efficiency under mild conditions for the oxidation of aromatic, aliphatic, and allylic secondary alcohols.